2015
DOI: 10.1371/journal.pone.0143622
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid and Eicosapentaenoic Acid Metabolism in Juvenile Atlantic Salmon as Affected by Water Temperature

Abstract: Salmons raised in aquaculture farms around the world are increasingly subjected to sub-optimal environmental conditions, such as high water temperatures during summer seasons. Aerobic scope increases and lipid metabolism changes are known plasticity responses of fish for a better acclimation to high water temperature. The present study aimed at investigating the effect of high water temperature on the regulation of fatty acid metabolism in juvenile Atlantic salmon fed different dietary ARA/EPA ratios (arachido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 78 publications
6
37
0
Order By: Relevance
“…In agreement, several recent studies have further demonstrated that balanced ARA and EPA are more critical than either individual FA in terms of growth and other metabolic processes further highlighting the need for understanding the optimal LC-PUFA balance (Norambuena et al, 2015;Norambuena et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In agreement, several recent studies have further demonstrated that balanced ARA and EPA are more critical than either individual FA in terms of growth and other metabolic processes further highlighting the need for understanding the optimal LC-PUFA balance (Norambuena et al, 2015;Norambuena et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Glencross and Rutherford (2011) reported disproportionate EPA and ARA retention in barramundi however this was likely an effect of the increasing DHA level in combination with either EPA or ARA. Atlantic salmon were also shown to conserve ARA (Norambuena et al, 2015) while Senegalese sole attempt to synthesise ARA when dietary supply is limited (Norambuena et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evidence suggests that the synthesis of 20:4n-6 is correlated with immune responses at sub-optimal water temperatures (Norambuena et al 2015). Therefore, the near optimal water temperature experienced during the current trial (Handeland et al 2008;Stehfest et al 2017) were not expected to elicit endogenous 20:4n-6 synthesis in response to temperature stress.…”
Section: Discussionmentioning
confidence: 88%
“…That said, dietary treatments had some variability, albeit small, in their 20:4n-6 content, varying from 1.1 to 6.3 g/kg of lipid, and diets containing lower levels of 20:4n-6 appear to induce in vivo 20:4n-6 biosynthesis (as indicated by increased apparent enzyme activity of Δ-5 desaturase bioconverting 18:2n-6-20:4n-6 in fish fed the NC and DHA-50 diets) to satisfy physiological demand not met through direct consumption. Given that dietary levels of 20:4n-6 were somewhat lower than those typically recommended or observed in feeds for Atlantic salmon and other species (~10 g/kg) [23,[50][51][52] this is perhaps an expected compensatory response. Nonetheless, it would be interesting to directly test whether the apparent sparing effect of SFA and MUFA on n-3 LC-PUFA also extends to n-6 LC-PUFA like 20:4n-6.…”
Section: Discussionmentioning
confidence: 89%